Screening of linseed (Linum usitatissimum L.) germplasm under epiphytotic conditions against major foliar diseases: SCREENING OF LINSEED GERMPLASM UNDER EPIPHYTOTIC CONDITIONS AGAINST FOLIAR DISEASES - K AJITHKUMAR; ASMA HOMBAL; A S SAVITHA; S T YENJERAPPA; K SHIVAKUMAR; M R GOVINDAPPA; D KRISHNAMURTHY (Journal of Oilseeds Research, 2020)
A set of 258 linseed germplasmaccessions were evaluated for major foliar diseases under epiphytotic conditions at AICRP linseed experimental block, Main Agricultural Research Station, Raichur during rabi 2019-20. Among the tested germplasm none of the lines were completely free from powdery mildew and Alternaria blight infection. The germplasm accession 20204 showed resistance for powdery mildew but no resistant source is recorded against Alternaria blight. Under moderately resistant group, 19801 and 20216 showed resistance to both Alternaria blight and powdery mildew. Twenty germplasm lines were identified against powdery mildew disease. The rest of the germplasm were moderately susceptible, susceptible or highly susceptible to powdery mildew and Alternaria blight infection.